Language as a branding tool - Norlyk, Birgitte (Language at Work - Bridging Theory and Practice, 2010)
Branding normally concerns products or corporations. Coca-Cola is a strong product brand. Applecombines a strong product brand with a unique corporate brand. In the modern businessenvironment, however, the concept of branding now encompasses the branding of managementphilosophies and management activities as reflected in the branding of the popular managementphilosophy of Lean. Language, metaphors and special lexical choices play an important factor in thebranding of Lean management as unique and innovative.